(untitled) (Research, Society and Development, 2024)
The rapid changes in social interactions and the easy access to information brought by technological advances require that professors rethink and rebuild teaching to maintain its quality. Active methodologies have been used to ensure the development of essential skills in professionals to deal with the current challenges and demands of the job market. This study presents the use of active project-based methodologies with undergraduate and postgraduate engineering students at the Federal University of Minas Gerais. This study aims to report on the implementation of a pilot plant for the causticizing stage of the pulp and paper Kraft Process and the development of two prototypes of industrial sludge drying equipment using solar energy and to evaluate the impact of the activities on the professional training of the people involved and the development of skills and competencies expected of engineering professionals according to the National Curriculum Guidelines, such as the ability to work in teams. The students could apply their technical knowledge in real situations in an interdisciplinary and multidisciplinary collaborative environment that encourages the resolution of complex engineering problems innovatively, with a holistic and humanistic vision that also considers social and sustainable aspects. They also demonstrated increased motivation and experienced the connection between industry and academia, which is essential to demonstrate the applicability of the techniques learned during the courses.